Expression of lipid metabolism- related genes, body composition and inflammation: Effects of sodium butyrate supplementation in subjects with obesity - Parichehr Amiri; Seyed Ahmad Hosseini; Maryam Saghafi-Asl; Amin Akbari-Naserkiadeh; Seyedeh Asal Jenani Zavieh; Sara Arefhosseini; Samira Asghari; Neda Roshanravan (Journal of Functional Foods)
Nowadays, the overwhelmed global prevalence of obesity has been emerged as the main cause of chronic non-communicable diseases. Microbiome-derived short-chain fatty acids, particularly sodium butyrate (NaBu) has been presented a plethora of pharmacological features in the treatment of metabolic conditions. The present triple-blind, randomized clinical trial examined the effects of NaBu supplementation on the expression of lipid metabolism- related genes in peripheral blood mononuclear cells, body composition compartments and serum high-sensitivity C-reactive protein (hs-CRP) in subjects with obesity. Fifty obese subjects were randomly allocated into either NaBu (600 mg/day) or placebo (carboxymethyl cellulose 600 mg/day) group along with hypocaloric diet for 8 weeks. At the end of the trial, the mRNA expression levels of adiponectin receptor-1, adiponectin receptor-2 and uncoupling protein-3, significantly increased in NaBu group to almost two-fold higher levels, compared with placebo group (p = 0.030, p = 0.030 and p = 0.010, respectively). Moreover, body composition compartments improved significantly in NaBu arm, in terms of reductions in fat mass (p = 0.027) and visceral fat (p = 0.026) as well as increases in fat-free mass (p = 0.032). Serum hs-CRP levels markedly decreased in NaBu group, while inter-group differences were non-significant. Taken together, NaBu supplementation could exert favorable anti-obesity effects through molecular pathways, while further research is recommended.This study was registered in Iranian Registry of Clinical Trials (https://irct.behdasht.gov.ir/user/trial/56967/view), (IRCT20190303042905N3).